Неконсистентный и маргинальный — два определения одного статуса - Матусевич, В. (Iнститут соціології НАН України, 2009)
Inconsistency and marginality are considered in modern sociology as different and unrelated phenomena, each of which has its own history of elaboration, conceptual and methodical principles. G.Lenski was first who have paid proper attention to these phenomena and noticed, that an individual with low consistent status is marginal with characteristic for him social and psychological features. In the sequel, this thesis seems to be falling on deaf ears with a view to conceptual comprehension and proper methodical embodiment. So, it did not result in studies of inconsistency and marginality as distinct but coherent descriptions of one status. In the article, an attempt to comprehend this connection as typically-causal is undertaken. The inconsistency is interpreted as a cause, and marginality is viewed as a result within this relation. At the same time, they both are understood as two definitions one status. Such approach makes it possible to unite theoretical and methodical facilities of these trend of research, as well as to trace the influence of separate descriptions of inconsistency on derived from them features of marginality. In particular, it results in dualism of marginal status, its similarity with other abutting upon him statuses by some status characteristics, dualism of attitudes of its bearers. The adjusted causal relation between inconsistency and marginality point out the perspective of further studies on this subject matter.